Three consecutive pregnancies having arthrogryposis multiplex congenita - Juneja, Sunil K.; Tandon, Pooja; Garg, Shirin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Arthrogryposis Multiplex Congenita is a syndrome or disorder that presents with multiple congenital joint contractures at birth. It is X-linked recessive disorder, non-progressive and is of variable severity. Here is a case report with three consecutive pregnancies having fetus affected with Arthrogryposis Multiplex Congenita (AMC) diagnosed antenatally. Arthrogryposis Multiplex Congenita affects 1 in 3000 live births. During embryogenesis, joint development is normal. Motion is essential for the normal development of joints and surrounding structures. Fetal akinesia causes extra connective tissue to develop around the joint. This results in fixation of the joint and a further increase in the contracture. Earlier in pregnancy the contractures form, worse is the prognosis.